Exploring knowledge bridging and translation in lesson study using an inter-professional team. Issue 3 (11th July 2016) - Norwich, Brahm; Koutsouris, George; Fujita, Taro; Ralph, Thomas; Adlam, Anna; Milton, Fraser
Abstract : Purpose: – It is argued that the issues of translating basic science, including knowledge from neuroscience, into relevant teaching are similar to those that have been experienced over a long period by educational psychology. This paper proposes that such a translation might be achieved through lesson study (LS), which is an increasingly used technique to stimulate teacher enquiry. To explore these issues, the purpose of this paper is to present the findings from a modified LS approach that involved psychologists and mathematics lecturers working together with school-based teachers to prepare a series of lessons on mathematics. Design/methodology/approach: – The LS team review and planning meetings and subsequent interviews were recorded and analysed for common themes, with reference to patterns of knowledge bridging. Particular attention was paid to translational issues and the kind of knowledge used. Findings: – Overall, there was some successful bridging between theory and practice, and evidence of translation of theoretical knowledge into relevant teaching practice. However, the analysis of the team's interactions showed that relatively little involved a useful applied neuroscience/neuropsychology element, whereas other psychological knowledge from cognitive, developmental, educational and clinical psychology was considered more relevant to planning the LS. Originality/value: – This study illustrates how reference to brain functioning has currently little specific to contribute directly to school teaching, but it can arouse increased interest in psychological processes relevant to teaching and learning. This approach reaffirms the central role of teacher-led research in the relationship between theory and practice. The findings are also discussed in relation to the SECI model of knowledge creation.